URBANIZATION: INTER-RELIGIOUS HARMONIZATION IN TUMPUKAN VILLAGE, KLATEN, CENTRAL JAVA - Mahsusi Mahsusi; Syihaabul Hudaa; Nuryani Nuryani (Balai Penelitian dan Pengembangan Agama Jakarta, 2022)
Urbanization is seen as having a big role in changing people's attitudes. This happens because during the urbanization period, rural communities experience a transition in behavior, culture, and even religion in the environment where they live. The real problem that occurs in people who have done a lot of urbanization is the loss of their local identity. The tradition that has been followed by the community before urbanization has undergone changes after urbanization. The purpose of writing this article is to examine how the urbanization that is mostly carried out by the people of Tumpukan Village towards the harmonization of inter-religious communities. This research belongs to the descriptive qualitative type using a direct action approach using interviews, recording, and data analysis from local village officials. The results of this study found that the people of Tumpukan Village, despite their different religions, still uphold tribal and kinship loyalty. Their mutual cooperation was evident during the pandemic when many people died from various religions. Those who help with the funeral process view the victims of covid-19 as human beings regardless of their religion. In other words, although there is a lot of urbanization in Tumpukan Village, their sense of gotong royong and locality are not lost. In addition, the village community still adheres to the beliefs inherited from their ancestors as local wisdom that must be maintained regardless of their religion.